Decoding maternal genetic background of Chinese Tujia people through extensive mitochondrial genome analyses - Chen, Chong; Chen, Man; Luo, Lintao; Zhu, Ying; Chen, Hongbing; Zhao, Minzhu; Cao, Yuhang; Li, Yongguo; Lan, Li; Shen, Chunmei; Li, Jianbo (Frontiers in Ecology and Evolution, 2025)
IntroductionThe Tujia ethnic group, belonging to the Tibeto-Burman linguistic family, predominantly resides in the mountainous regions of central and southern China. Despite their substantial population size and rich historical background, the maternal genetic characteristics of the Tujia, especially regarding the complete mitochondrial genome, remain insufficiently studied.MethodsIn this study, we obtained 131 complete mitochondrial sequences from healthy, unrelated Tujia individuals in Chongqing utilizing MPS technology. To facilitate population genetic comparisons, we selected 8,861 global modern individuals and 1,635 ancient individuals as reference datasets.ResultsOur findings revealed that the Chongqing Tujia exhibited significant representations of maternal haplotypes prevalent in East Asia, particularly in southern East Asia. Phylogenetic tree and Bayesian analyses indicated that the Tujia likely experienced several distinct population expansions during their formation. Moreover, genetic analyses revealed intimate matrilineal relationships between the Tujia and neighboring populations, such as Han populations. Additionally, the Tujia also demonstrated maternal genetic connections to geographically distant populations, such as those from Tibeto-Burman linguistic family. For ancient reference populations, close maternal genetic affinities between Tujia and populations from the Yellow River Basin were revealed, particularly those from the Late Neolithic to Early Bronze Age.DiscussionThe complex maternal genetic architecture of the Chongqing Tujia was elucidated based on complete mitochondrial genomes. Recent population admixture or ancient genetic imprints may play roles in shaping the genetic diversity patterns of the Tujia group. This study enhances our understanding of the maternal genetic background of Chongqing Tujia, offering valuable insight into the genetic diversity and broader evolutionary history of Chinese ethnic minorities.